The New Frontier of Religion and Science - Hick, J. author. aut Link
XII, 228 p.
Keywords: This is the first major response to the challenge of neuroscience to religion. It considers eastern forms of religious experience as well as Christian viewpoints and challenges the idea of a mind identical to, or a by-product of, brain activity. It explores religion as inner experience of the Transcendent, and suggests a modern spirituality.